BEHAVIORAL MANAGEMENT IN DENTAL TREATMENT FOR CHILDHOOD AUTISM: (CASE STUDY) - Muhammad Chair Effendi; Sri Susilawati; Mirna Febriani; Agus Susanto; Lisda Damayanti; Anne Agustina S; Inne S. Sasmita (Jurnal Ilmiah dan Teknologi Kedokteran Gigi, 2022)
Background: Autism Spectrum Disorder (ASD) or autism is a disorder that occurs during brain development characterized by deficiencies in social behavior and nonverbal interactions such as lack of eye contact, facial expressions, and body movements before a child is three years old. Autism Spectrum Disorder (ASD) is not a single disorder and is generally considered a multi-factorial disorder caused by the interaction of genetic and non-genetic factors. Lack of social behavior includes avoiding eye contact, difficulty controlling emotions or understanding the emotions of others, and limiting the range of activities and interests. Case report: A patient, female, 7 years and 4 months complained that the maxillary front teeth shake and want to be removed. Patients are suspected of having symptoms of autism since the age of 2 years and have started screening at that age until finally diagnosed with autism. Autism in patients, in this case, is suspected of autism from genetic factors. Conclusion: People with autism require special examination and treatment regarding the health of their teeth and mouth. These actions require cooperation between dentists and pediatricians or psychologists or other related disciplines so that the desired end results can be achieved as well as possible.